Enhanced cyclic deformation responses of ultrafine-grained Cu and nanocrystalline Cu–Al alloys - An, X.H.; Wu, S.D.; Wang, Z.G.; Zhang, Z.F. (Acta materialia, 2014)
Cyclic deformation responses of ultrafine-grained (UFG) Cu and nanocrystalline (NC) Cu–Al alloys produced by equal channel angular pressing were investigated systematically by applying low-cycle fatigue (LCF) and high-cycle fatigue (HCF) tests. Based on the dependence of the fatigue life (Nf) on the total strain amplitude (Δεt/2) and stress amplitude (Δσ/2) in comparison with that of UFG Cu, the LCF life and HCF strength, especially fatigue endurance limits, of NC Cu–Al alloys, were enhanced strikingly at the same time as their stacking fault energies (SFE) decreased. These upgraded fatigue performances with lowering of the SFE in NC Cu–Al alloys can be attributed not only to the simultaneous increase in their monotonic strength and ductility on the macroscale, but also to the crucially decreased cyclic softening behavior on the microscale. It was found that substantial grain growth and large-scale shear bands, both of which are essential ingredients, resulting in significant cyclic softening and then deterioration in the LCF life of UFG and NC materials, were reduced advantageously on decreasing the SFE in NC Cu–Al alloys. Moreover, the dominant fatigue damage micromechanism was also transformed inherently from extensive grain boundary (GB) migration in UFG Cu to other local GB activities such as atom shuffling or GB sliding/rotation in NC Cu–Al alloy with low SFE.